PEMBELAJARAN PAI BERBASIS PROYEK (PROJECT BASED LEARNING) DALAM PEMBENTUKAN SIKAP RELIGIUS PESERTA DIDIK DI SMK ARYASATYA TEKNOLOGI PURWOKERTO - Teguh Wiyono; Muta Ali Arauf; Shodiq Khalidy; Rina Sangadah (Hijri, 2026)
Project-based Islamic Religious Education (Project Based Learning/PjBL) is an innovative pedagogical approach considered relevant in addressing contemporary learning needs in Vocational High Schools (Sekolah Menengah Kejuruan/SMK), particularly in enhancing students’ active engagement while fostering sustainable religious attitudes. This study aims to describe and analyze in depth the implementation of project-based Islamic Religious Education in shaping students’ religious attitudes at SMK Aryasatya Teknologi Purwokerto. The research employed a qualitative approach with a case study design. Data were collected through direct classroom observations, in-depth interviews with Islamic Religious Education teachers and students, and documentation analysis related to the planning and implementation of project-based learning activities. The findings indicate that the application of the Project Based Learning model in Islamic Religious Education creates a more contextual, participatory, and meaningful learning environment. Through project activities, students not only develop conceptual understanding of religious materials but also internalize Islamic values, including faith, discipline in religious practices, responsibility, cooperation, and social awareness. Therefore, project-based Islamic Religious Education is proven to be effective in fostering students’ religious attitudes in a more active, reflective, and practical manner, both within the school environment and in their daily social lives.